Left-dominant arrhythmogenic cardiomyopathy: an association with desmoglein-2 gene mutation—a case report. Issue 6 (23rd June 2021) - Lao, Nicole; Laiq, Zenab; Courson, Jeffrey; Al-Quthami, Adeeb
Abstract: Background: Desmosomes are specialized intercellular adhesive junctions of cardiac and epithelial cells that provide intercellular mechanical coupling through glycoproteins, one of which is desmoglein (DSG). DSG-2 mutations are frequently associated with biventricular arrhythmogenic cardiomyopathy (ACM). We report a case of left-dominant ACM in a patient who initially was misclassified as dilated cardiomyopathy (DCM). Case summary: A 28-year-old-woman was found to have a moderately reduced left ventricular (LV) systolic function and frequent premature ventricular contractions (PVCs). Targeted genetic testing revealed a heterozygous likely pathogenic variant associated with ACM in exon 15 of the DSG-2 gene (c.3059_3062del; p.Glu1020Alafs*18). Subsequent cardiac magnetic resonance (CMR) imaging showed epicardial and mid-myocardial fatty infiltration involving multiple LV wall segments, multiple areas of mid-myocardial fibrosis/scar, regional dyskinesis involving both ventricles, and an overall reduced left ventricular ejection fraction. The patient's right ventricular (RV) cavity size and overall RV systolic function were normal. Based on the patient's frequent PVCs, family history, fibrofatty myocardial replacement in multiple LV segments, and dyskinetic motion of multiple ventricular wall segments (predominantly affecting the LV), the patient was diagnosed with left-dominant ACM. Discussion: Identifying a likely pathogenic mutation associated with ACM in a patient with ventricular arrhythmias and a family history of sudden cardiac death increased the possibility of ACM. Subsequent CMR imaging confirmed the diagnosis of left-dominant ACM by demonstrating regional biventricular dyskinesia and a characteristic pattern of fibrofatty myocardial replacement. Our case highlights the importance of targeted genetic testing and advanced cardiac imaging in distinguishing left-dominant ACM from DCM.